Application of Interval Arithmetic in the Evaluation of Transfer Capabilities by Considering the Sources of Uncertainty - Prabha Umapathy; C. Venkataseshaiah; M. Senthil Arumugam (Discrete Dynamics in Nature and Society)
Total transfer capability (TTC) is an important index in a power system with large volume of inter-area power exchanges. This paper proposes a novel technique to determine the TTC and its confidence intervals in the system by considering the uncertainties in the load and line parameters. The optimal power flow (OPF) method is used to obtain the TTC. Variations in the load and line parameters are incorporated using the interval arithmetic (IA) method. The IEEE 30 bus test system is used to illustrate the proposed methodology. Various uncertainties in the line, load and both line and load are incorporated in the evaluation of total transfer capability. From the results, it is observed that the solutions obtained through the proposed method provide much wider information in terms of closed interval form which is more useful in ensuring secured operation of the interconnected system in the presence of uncertainties in load and line parameters.